Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review: 48



Work Step by Step

$\frac{x^{\frac{1}{4}}x^{-\frac{1}{2}}}{x^{\frac{2}{3}}}$ =$\frac{x^{\frac{1}{4}-\frac{1}{2}}}{x^{\frac{2}{3}}}$ =$\frac{x^{\frac{1-2}{4}}}{x^{\frac{2}{3}}}$ =$\frac{x^{\frac{-1}{4}}}{x^{\frac{2}{3}}}$ =$x^{-\frac{1}{4}-\frac{2}{3}}$ =$x^{\frac{-3-2(4)}{12}}$ =$x^{\frac{-11}{12}}$ =$\frac{1}{x^{\frac{11}{12}}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.